Conformational prediction and circular dichroism studies on ribosomal protein S4 from Escherichia coli. - Allen, S H (1978)
The conformation of ribosomal protein S4 from Escherichia coli has been studied by circular dichroism (CD) and shown to possess unique conformation free in solution. The near ultraviolet spectrum suggests the existence of unique tertiary structural environment for the aromatic amino acid residues. The far ultraviolet spectrum gives an estimation of its secondary structure which is 32% alpha-helix and 14% beta-structure in reconstitution buffer at 25 degrees C. The conformation of S4 has been predicted from its sequence, and two models are presented here. An attempt is made to correlate these two molecular models with the available physicochemical data concerning the shape, conformation, and possible RNA binding site of protein S4.